Structural Identification of an 18-Story RC Building in Nepal Using Post-Earthquake Ambient Vibration and Lidar Data - Yu, Hanshun; Mohammed, Mohammed A.; Mohammadi, Mohammad E.; Moaveni, Babak; Barbosa, Andre R.; Stavridis, Andreas; Wood, Richard L. (Frontiers in Built Environment, 2017)
Few studies have been conducted to assess post-earthquake performance of structures using vibration measurements. This paper presents system identification and finite element modeling of an 18-story apartment building that was damaged during the 2015 Gorkha earthquake in Nepal. In July 2016, a few months after the earthquake, the authors visited the building and collected its ambient acceleration response. The recorded data are analyzed and the modal parameters of the structure are identified using an output-only system identification method. A linear finite element model of the building is also developed based on the geometry of the building and its material properties to estimate numerically its dynamic characteristics. The identified modal parameters are compared to those of the model to identify possible shortcomings of the modeling and identification approaches. The identified natural frequencies and mode shapes of the first two vibration modes are in good agreement with the model.